The Influence Of Parents In Increasing Learning Motivation On Student Achievement (Children) - Ernawati Ernawati; Zaenal Arifin; Masykur Mansyur (Al-Madrasah: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
This research formulates the problem of The Influence of Parents in Increasing Learning Motivation Towards Student Achievement (Children) At Mts Miftahul Ulum, Research is carried out at Madrasah Tsanawiyah (MTs) Miftahul Ulum Cikarang Bekasi which amounted to 33 students who were designated as members of the population who were also sample members after the withdrawal of samples with saturated sampling techniques, so that data was obtained using  instruments for analysis with inferential statistical techniques correlational effectiveness test. As for the students numbered 135 students for the entire population, but the authors only took samples from class VII.as a sample. The results showed that parents' motivation for their children was the highest accumulated data by 55.52% of respondents choosing categories often, so it can be concluded that students generally claim that their parents' motivation is very high in fostering their children. Student learning achievement was obtained an average of 74.96 which if interpreted according to the average categorization table of student grades then contained in the high category. Thus, H0 was rejected and H1 was accepted which means that parental motivation has a significant effect on student achievement in English in Madrasah Tsanawiyah (MTs) Miftahul Ulum Cikarang Bekasi.